Why South Vietnam fell - Joes, Anthony James (Lexington Books, 2014)
Examination of the administration of President Ngo Dinh Diem of South Vietnam and how the country survived all Communist attempts to overthrow it until the U.S. Congress allowed the anti-Communist population to be conquered by the North.